LEGAL ASPECTS OF SECURITY OF THE MILITARY INFRASTRUCTURE VERSUS ITS SECURITY EFFECTIVENESS - RADZIEJEWSKI Ryszard (2013)
The author has analysed legal legislatives that regulate security of the military infrastructure. Basing on it, he put forward the thesis that efficiency of operation of military administration in this range is unsuitable to contemporary threats of this infrastructure. And is also ineffective in protection of the infrastructure.